Fe3O4-ZnO:V Nanocomposites with Modulable Properties as Magnetic Recoverable Photocatalysts - Ana Varadi; Cristian Leostean; Maria Stefan; Adriana Popa; Dana Toloman; Stela Pruneanu; Septimiu Tripon; Sergiu Macavei (Inorganics, 2024)
Since semiconductor-based photocatalysis uses solar energy as a free and sustainable energy source and inoffensive photocatalysts, it has been found to be a promising green approach to eliminating dyes, antibiotics, and other pharmaceuticals from water that has been contaminated. In this study, a distinctive magnetic separable Fe3O4-ZnO:V photocatalyst is reported. ZnO:V semiconductors have been produced by seed-assisted growth over preformed magnetite to develop Fe3O4-ZnO:V nanocomposites. The results indicated nanocomposites with the structure of Fe3O4, ZnO:V, according to the findings of the XRD, XPS, and HRTEM investigations. Additionally, magnetic studies revealed at room temperature, the nanocomposite exhibited superparamagnetic properties. Electrochemical Impedance Spectroscopy (EIS) was employed to characterize the ability of the Fe3O4-ZnO:V nanocomposites to transfer electrons. Furthermore, the impact of dopant on optical characteristics was evaluated. When exposed to rhodamine B (RhB), all the samples exhibited photocatalytic activity. Through the use of an ESR experiment and the spin-trapping technique, the existence of reactive oxygen species (ROS) at the solid–liquid interface was demonstrated, and their impact on the samples’ photocatalytic activity was highlighted. After recycling, XRD, XPS, and SEM were performed to illustrate the stability of the material. The impact of V doping on the morphologic, structural, and compositional properties of magnetically separable Fe3O4-ZnO:V composite nanoparticles for photocatalytic applications is the innovative aspect of our work.